PELATIHAN PEMBENTUKAN KEPRIBADIAN YANG SEHAT DAN POSITIF MELALUI TERAPI INNER CHILD KEPADA MAHASISWA JURUSAN ADMINISTRASI BISNIS POLITEKNIK NEGERI MANADO - Nisba Silvana; Selfy Manueke; Juliet P.T. Makinggung (JURNAL DAYA-MAS, 2024)
This inner child therapy training aims to make students majoring in Business Administration at Politeknik Negeri Manado able to make peace with the inner child trauma experienced so that they can develop a healthy and positive personality. The problem faced is that about 44 students experience an inner child. This can be seen from the condition of students who show unstable emotional turmoil in the classroom. The inner child is the result of bad experiences or events in the past that have not been resolved properly. The negative effects of the inner child students feel are difficulty knowing themselves well, lack of ability to understand their potential, lack of trust in themselves and others, quickly feeling disappointed with various life situations, and lack of ability to control emotional turmoil. The purpose of meditation is for each student to be able to accept and make peace with their inner child trauma, besides that meditation which is done regularly can reduce the level of depression, a person's emotional condition tends to be more stable, able to generate positive energy so that they can live life better. Based on the follow-up survey of the training results, it was found that around 81.25% of students were able to make peace with their inner child.